US foreign policy and democracy promotion from Theodore Roosevelt to Barack Obama - Bouchet, Nicolas; Cox, Michael 1947-; Lynch, Timothy J. 1969- (Routledge studies in US foreign policy, 2013)
For more than a century at least, American presidents have been driven by deep historical and ideological forces to conceive US foreign policy in part through the lens of democracy promotion. This book offers a collection of articles that debate how far democratic aspirations have been realized in actual foreign policies.